HUBUNGAN SUPERVISI KEPALA RUANGAN DENGAN METODE ELECTRONIC NURSING DOCUMENTATION PADA ERA PANDEMI COVID-19 DI RSUD PASAR MINGGU JAKARTA - Dila Sari Putri (2021)
The application of electronic nursing documentation makes it difficult for nurses to adapt to the system. It takes the role of the head of the room in overcoming this problem. Supervision carried out by the head of the room can affect the quality of electronic nursing documentation which is the development of a computerized system that has been made by the hospital in recording nursing care. The purpose of this study was to identify the relationship between the supervision of the head of the room and the implementation of nursing care using the Electronic Nursing Documentation method during the Covid-19 Pandemic Era in the Inpatient Room of Pasar Minggu Hospital, Jakarta. This study uses a descriptive correlation research design using a cross sectional approach. The sampling technique used was purposive sampling with a total sample of 129 nurses. Collecting data using a questionnaire and analyzed using the Chi-Square test. The results of statistical tests showed that there was a significant relationship between gender (p=0.016) and supervision (p=0.000) with electronic nursing documentation. There was no relationship between age (p=0,275), marital status (p=0,272), education level (p=0,504), and years of service (p=0,275) with electronic nursing documentation. The conclusion of this study is that there is a significant relationship between the supervision of the head of the room with the method of electronic nursing documentation. The recommendation of this study is that hospital management is expected to be able to periodically supervise electronic nursing documentation, even in the current state of the Covid-19 pandemic.